La place de l’artisanat en Gaule romaine du Centre, Nord-Ouest et Centre-Ouest (province de Lyonnaise et cités d’Aquitaine septentrionale) - Alain Ferdière (Revue Archéologique du Centre de la France)
An inventory, as complete as possible, of literal, epigraphic, iconographic and especially archaeological clues of craft industry in civitates of Gallia Lugdunensis and of the north-eastern boundary of Gallia Aquitania, from the first century BC to the fifth century AD, enabled us to study the location of handcraft activities of artifact production. Thus, we can make some suggestive remarks, on the one hand regarding the capital cities of the civitates, the secondary towns and the countryside relative participation in this subject, on the other hand regarding the location of the different craft industries, especially the successive phases of their operative networks.